Service Quality And Availability To Improve Client Satisfaction - Saskia Nurul Amalia; Richa Puspita Nur Musthaqfiroh; Farah Ayuningtyas (CV. AFDIFAL MAJU BERKAH, 2024)
The Effect of Service Quality and Facilities on Customer Satisfaction at AHASS Bintang Motor Jaya Plered Customers